The Use of YouTube based Interactive Learning Media in Giving English Subject Material for Middle School Students - Tanti Tiara; Yousef Bani Ahmad; Abdul Kodir Al-Baekani (Universitas Muhammadiyah Enrekang, 2021)
The research objective is to see eight grade students’ perception of the use of interactive learning media based on YouTube in giving English subject material. The reason of researcher did this research is because the educators at the junior high school use YouTube as a learning medium which is expected so that students can understand the material being studied, so that students can continue to follow the teaching and learning process during the pandemic, especially in English subjects. This study used a qualitative research with narrative inquiry approach and thematic analysis to see the response of the use of YouTube. In order to get accurate results, the researchers used questionnaire and interviews. The subjects of this study were 8th grade students in one of junior high school in Karawang who are familiar with using YouTube as a media. Based on the results of the study, that had been conducted on the use of YouTube-Based interactive media to giving English material was that 4 out of 5 eighth grade students at one of junior high school in Karawang liked and were happy with the way teachers delivered material through YouTube videos during this pandemic because they become the focus of learning and the material becomes easy to understand.